Towards Perception of Productivity: The Dilemma of Domesticating ICT in Office Life - Juntiwasarakij*, Suwan (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
It has been almost half a century that information technology was introduced as a tool for a company to achieve organizational performance and productivity. The technology was expected to set human free and thus do more creative things. However, the outcomes were reportedly mixed. This study aimed to review contemporary literature on the impact of computer technology on office work by employing social technical system as theoretical lens to investigate the phenomenon. The consequences of domestication ICT technology to work place were analyzed, the insights were drawn from the findings, and in the end the discussion was offered. Keywords: information communication and technology, job burnout, office automation, productivity, organization *Corresponding author: Email: kjsuwan@kmitl.ac.th,